Blocking Dangerous Content in Electronic Communications Networks: Evidence from Netherlands, United States and Singapore - Mulyawarman, I Gede Adhi; Arya Sumerta Yasa, Putu Gede; Cait, Lamberton (Journal of Human Rights, Culture and Legal System, 2024)
In recent years, the blocking of internet sites with harmful content or those deemed to be (illegal content) has increased. The policy of blocking dangerous sites has pros and cons regarding freedom of expression. Blocking is considered to be carried out to control citizens' expression, which can impact all areas, especially freedom of opinion, which can be seen as a threat to certain parties. This research aims to compare criminalization policies for blocking dangerous content in electronic communications networks in the Netherlands, the United States, and Singapore and provide thoughts on law enforcement models for blocking dangerous content in more democratic electronic communication networks. This is normative legal research using a law and case approach and comparing several countries. The conceptual approach is directed at the concept of a democratic state and the protection of human rights to formulate relevant policy models. The results of blocking studies in the Netherlands, The USA, and Singapore already have regulations and policy directions for blocking dangerous content, or at least rules regarding law enforcement for cybercrime. The difference is in the level of sensitivity to the specifications of existing problems. The policy model for blocking dangerous content with special regulations outside the Criminal Code must be carried out in a non-repressive manner so that it does not violate the ultimum remedium principle and becomes over-criminalized. The formulation of policy model of all crime prevention plans using the criminal law system, which pays attention to the problem of formulating criminal acts (criminalization), criminal responsibility, and criminal regulations and punishment.